Descriptive Study: Cross-Nation Marriage Family between Foreign Citizen and Local Citizen in Timbang Jaya Village, Bahorok Sub-District, Langkat Regency - Sihar Pandapotan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study is about cross-nation  marriage aiming to understand the factors of cross-nation marriage happened, understand the difficulties in parenting pattern introduced in cross-nation marriage, understand how the implication of daily life’s pattern applied, and understand the difficulties faced by the parents who come from different cultural backgrounds in running household. Meanwhile the result of this study is that there were many differences in pattern of life which is applied in their families, starting from the language used in daily, food consumed, and the way of thinking in their families. Although the status of citizenship of the foreign citizens were the same from the several families studied, in running their lifes, there were some differences based on their personalities and neighborhoods, some were ease to assimilated with the society around, some were hard to adapt with the society and the cultures of Indonesia, in general. Moreover, the general difference between west culture and east culture is the west culture tends to own more freedom and the east culture tends to limit the freedom of a child in having a decision. According to these phenomena, the author could see how their interactions with the society in the neighborhood were, how their status were, how their behavior in practicing the custom and culture and pattern of daily life was. In this study, the author used the qualitative method as a reference to get the data significantly from the main informants. Furthermore, the author used the technique of collecting data by interviewing to get the more comprehensive data.